2020
DOI: 10.1128/msystems.00539-20
|View full text |Cite
|
Sign up to set email alerts
|

Negative Interplay between Biofilm Formation and Competence in the Environmental Strains of Bacillus subtilis

Abstract: Environmental strains of the soil bacterium Bacillus subtilis have valuable applications in agriculture, industry, and biotechnology; however, environmental strains are genetically less accessible. This reduced accessibility is in sharp contrast to laboratory strains, which are well known for their natural competence, and a limitation in their applications. In this study, we observed that robust biofilm formation by environmental strains of B. subtilis greatly reduced the frequency of competent cells in the bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 66 publications
(125 reference statements)
1
9
0
Order By: Relevance
“…In the wild type strain GP2630, about 40% of the cells expressed GFP, similar to previously published results (She et al, 2020), and slightly higher numbers were obtained for the control strain lacking ComEC, which is not impaired in comK and subsequent comG expression. In contrast, the control strain lacking DegU showed decreased amount of GFP expressing cells as compared to the wild type (Figure 1), which reflects the role of DegU on the activation of comK expression.…”
Section: Comk-dependent and -Independent Functions Of Proteins Are Required For The Development Of Genetic Competencesupporting
confidence: 89%
“…In the wild type strain GP2630, about 40% of the cells expressed GFP, similar to previously published results (She et al, 2020), and slightly higher numbers were obtained for the control strain lacking ComEC, which is not impaired in comK and subsequent comG expression. In contrast, the control strain lacking DegU showed decreased amount of GFP expressing cells as compared to the wild type (Figure 1), which reflects the role of DegU on the activation of comK expression.…”
Section: Comk-dependent and -Independent Functions Of Proteins Are Required For The Development Of Genetic Competencesupporting
confidence: 89%
“…Biofilm is considered as a suppressor of lipopeptides (e.g., surfactin) synthesis, so disruption of biofilm formation is favorable for improving lipopeptides production ( Wu et al, 2019 ). Here, we knocked out several genes related to biofilm formation such as comK ( She et al, 2020 ), sigD ( Fan et al, 2016 ), dhbF (a gene of dhb operon for biosynthesis of siderophore) and fur (a repressor of dhb ) ( Oliveira et al, 2017 ; Pi and Helmann 2017 ), abrB and sinR (regulators to suppress biofilm formation) ( Newman et al, 2013 ; Klausmann et al, 2021 ), and sinI (a regulator to promote biofilm formation) ( López et al, 2009 ). Deletion of respective genes resulted in an obvious change of colony morphology and float pellicle, but only deletion of dhbF led to a significant increase of antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that natural competence could not transfer plasmids to undomesticated B. subtilis strains tested ( Figure 1 ). The result may be due to a lack of natural competence-related genes or the negative interplay between biofilm formation and competence ( She et al, 2020 ). Some strains may have competence inhibitor genes ( Konkol et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%